Research on the Impact of Digital Economy on Residents’ Consumption Upgrade: Taking Shanghai as an Example - Li, Sixuan; Liu, Bowen; Fang, Baoting; Zhang, Biyun (International Journal of Global Economics and Management, 2024)
In the information age, the development of the digital economy has brought increasingly important influences on residents’ consumption concepts, consumption scale, consumption methods, consumption structure, etc. This paper first summarizes the performance of the digital economy in driving the improvement of residents’ consumption methods and enriching consumption content, and constructs a theoretical model; then, based on the time series data of Shanghai from 2005 to 2022 , this paper empirically studies the impact of the development of the digital economy in Shanghai on residents’ consumption; finally, from the perspective of regional differences, this paper proposes effective paths and optimization policies for the digital economy to drive the expansion of consumption scale, optimize the upgrading of consumption structure, and promote economic development.